Clinical and radiological evaluation of nonvascularized cancellous iliac bone graft for the treatment of nonunited scaphoid fracture - Amr Abd El halem Amr (Wolters Kluwer Medknow Publications, 2021)
Purpose We evaluated the clinical and radiological outcome of pure cancellous iliac bone graft for the treatment of scaphoid nonunion. Patients and methods The subjects of this study were 30 patients who had a nonunited scaphoid fracture treated with pure cancellous iliac bone graft and casting between March 2015 and April 2019. The average follow-up period was 9 months. We performed open reduction through the volar approach with impaction of the fracture site with pure nonvascularized cancellous iliac bone graft and scaphoid cast for a period ranging from 1 1/2 to 3 months. Results Bony union was achieved in 29 of 30 patients. Nonunion occurred in only one patient.